The Phonetic Classification of ‘Inelegant Language’ in Sibawayhi’s Al-Kitab - ALAzzam, Mohamed; Awaad, Mohamed (Dirasat: Human and Social Sciences, 2021)
This paper implores what is evaluated and judged on a phonetic level as an inelegant and unconventional grammatical structure in Sibawayhi’s book, Al-Kitab (d. 180 H) according to its alignment with grammatical principles. This is achieved by justifying the factors of this unconventionality and limitations of its application. Subsequently, this research paper explores the scientific evaluation of inelegance as a judgment, specifically when gauging its evidence in the rhetoric of many early linguistic scholars and intellectuals. This impact is evident whether in this grammatical inquiry into Arabic linguistic standards and grammatical foundations, or in its structuring of standard spoken Arabic. This research paper’s innovative focus is in its expository and accurately identification of the factors leading to grammatical classifications as: inelegant; very inelegant; wrong; slightly inelegant. It also proposes inquiring into whether Sibawayhi’s classification is an attempt to categorize linguistic levels or is simply an employment of descriptive synonyms to attribute to inelegant linguistics.